Psychological Representations of Sound in Cinematic Drama (Maleficent, Mistress of Evil) as a model (Eurasian Journal of Humanities and Social Sciences, 2022)
The introduction of sound in the cinema is a revolutionary step that added a tremendous momentum to the film expression. Before the advent of sound, the film was unable to rise high because it had one element only, which is image, and since the connotation does not reproduce and does not refer to itself until after the establishment of its activities on the psychological side of the human self, especially since the sound, with its many expressive levels (dialogue, sound effects, music and silence), is able to send endless connotations, so it was necessary to research (the psychological representations of sound levels in cinematic drama), and to include the methodological framework that includes the research problem, the need for it and the goal of writing it and its time, place and objective limits, and the extraction and interpretation of terms for clarity and orientation to the right direction, and in the theoretical framework, it contains two topics, the first of which is entitled (sound and illusion) and the other (the psychology of voice narration in cinematic drama).It also included the research procedures and its society, the method on which the analysis was based, the approved analytical tool, as well as the analysis sample. Finally, the results came. May Allah grant us success.